Neuroeconomics in cooperatives: hierarchy of emotional patterns in the collective decision-making process for sustainable development - Zúñiga Aguilar, Isaac (2022)
The goal of this study is to determine the level of adaptation of agro-industrial cooperatives of small producers of alternative crops, and it considers the hierarchy of patterns to evaluate their systemic responses to accelerated change following the COVID-19 pandemic by evaluating the risk of their structures adapting to the digital environment. With a total of (n = 90) volunteer responders, the study is experimental, transactional, descriptive, and correlational, with a control group (CENFROCAFE) and an experimental group (ACEPAT) (24 producer partners, 14 producer managers, and 7 employees for each cooperative). In Step 1 (SOFT aspect), it measures the organizational memory (OM) of Y0 = 0.32 in the (control group) and Y1 = 0.59 in the (experimental group) by measuring hidden plots in the formal and informal interrelations of its members with the correlation of the holistic competencies of innovation. In Stage 2 (HARD aspect), the impact of the digital operational risk (DOR) is measured in the adaptation of the organization structure, which results in the control group with a Digital Operational Risk (DOR) = (3.4), which is “High” and greater than the experimental group with DOR = (3.3), which is “Moderate”. In conclusion, Hypothesis 1 is met with a greater adaptation of the experimental group, greater organizational memory, and lower digital operational risk, which reflects that the memory of the organization would reflect the temporal memories of the human brains of its members, and that, in the same way, its behavior could be predicted linearly.